Tobin LIVES: Integrating evolving credit market architecture into flow of funds based macro-models - John Duca; John Muellbauer (European Central Bank (ECB), 2013)
After the global financial crisis, there is greater awareness of the need to understand the interactions between the financial sector and the real economy and hence the potential for financial instability. Data from the financial flow of funds, previously relatively neglected, are now seen as crucial to the data monitoring carried out by central banks. This paper revisits earlier efforts to understand financial-real linkages, such those of Tobin and the Yale School, and proposes a modeling framework for analysing the household flow of funds jointly with consumption. The consumption function incorporates household income, portfolios of assets and debt held at the end of the previous period, credit availability, and asset prices and interest rates. In a general equilibrium setting, these all have to be endogenised and since households make consumption and housing purchase decisions jointly with portfolio decisions, there is much to be gained in modeling a household sub-system of equations. Major evolutionary structural change – namely the evolving credit architecture facing households – is handled by our `Latent Interactive Variable Equation System' (LIVES) approach. A byproduct is improved understanding of the secular decline in US saving rate, as well as of the household financial accelerator. Moreover, the models discussed in this paper offer new ways of interpreting data on credit, money and asset prices, which are crucial for central banks.
Keywords: B22; E21; E44; E51; G11; 330; Consumption; credit constraints; Finance and the real economy; financial crisis; household portfolios.